Identification and characterization of fungal species causing anthracnose disease on mango (Mangifera indica L. - Mohd Din, Siti Norliza (2016)
Mango (Mangifera indica L.) belongs to the family Anacardiaceae is grown primarily in Malaysia valued for local mango production and has high nutritional value. One of the major problem pre and post-harvest diseases on mango is anthracnose disease caused by many fungal species in the genus Colletotrichum. Symptoms of the disease included irregular, circular dark brown spot appear on the young leaves, flowers and fruits. In Malaysia, there is limited research on the composition of fungal species responsible for mango anthracnose. The objectives of this study are; 1) to isolate pure culture of fungal isolates causing anthracnose on mango fruits and leaves; 2) to identify fungal pathogens to species level based on morphological characteristics and polymerase chain reaction (PCR) protocol using ITS4 and ITS5 primers; and 3) to construct internal transcribed spacer (ITS) phylogeny of the fungal species using maximum likelihood analysis. To accomplish these objectives, symptomatic fruits were collected from five different mango trees at Taman Pertanian Universiti (TPU), Universiti Putra Malaysia. Infected tissues (5 x 5mm) from the lesions margin was being surface disinfected for 2 min with 10% Clorox and cultured on potato dextrose agar (PDA). The pure fungal isolates isolated from fruit lesions were identified by conidial and in vitro morphological characteristics according to Mordue et al.,(1971). The fungal isolates were sub-cultured by single spore isolation and the representative was characterized further. DNA genomic was extracted from fresh fungal mycelium by using protocol of DNeasy Plant Mini Kit from QIAGEN. The internal transcribed spacer (ITS) region of the ribosomal DNA was amplified using primers ITS4 and ITS5. The PCR product of the ITS was sequenced and analyzed using BLAST nucleotide query in GenBank. In this study, all fungal isolates match to the sequence of Colletotrichum asianum within C.gloeosporiodes species complex. This study is a significant step forward management recommendation in controlling anthracnose in mango production areas.